From Sharks to Yeasts: Squalene in the Development of Vaccine Adjuvants - Adélia Mendes; João Azevedo-Silva; João C. Fernandes (Pharmaceuticals, 2022)
Squalene is a natural linear triterpene that can be found in high amounts in certain fish liver oils, especially from deep-sea sharks, and to a lesser extent in a wide variety of vegeTable oils. It is currently used for numerous vaccine and drug delivery emulsions due to its stability-enhancing properties and biocompatibility. Squalene-based vaccine adjuvants, such as MF59 (Novartis), AS03 (GlaxoSmithKline Biologicals), or AF03 (Sanofi) are included in seasonal vaccines against influenza viruses and are presently being considered for inclusion in several vaccines against SARS-CoV-2 and future pandemic threats. However, harvesting sharks for this purpose raises serious ecological concerns that the exceptional demand of the pandemic has exacerbated. In this line, the use of plants to obtain phytosqualene has been seen as a more sustainable alternative, yet the lower yields and the need for huge investments in infrastructures and equipment makes this solution economically ineffective. More recently, the enormous advances in the field of synthetic biology provided innovative approaches to make squalene production more sustainable, flexible, and cheaper by using genetically modified microbes to produce pharmaceutical-grade squalene. Here, we review the biological mechanisms by which squalene-based vaccine adjuvants boost the immune response, and further compare the existing sources of squalene and their environmental impact. We propose that genetically engineered microbes are a sustainable alternative to produce squalene at industrial scale, which are likely to become the sole source of pharmaceutical-grade squalene in the foreseeable future.